Design of novel hexagonal s-band patches antenna array for RFID applications - Zohra Slimane; Mohammed Amin Rabah; Abdelhafid Abdelmalek; Kouther Yamani; Kaoutar Hachemi (Institute of Advanced Engineering and Science, 2022)
The design and study of the behavior of antennas adapted to radio-frequency identification RFID tags take on all their importance because they must respond to integration problems and therefore the need to design a structure with minimal dimensions, without however deteriorating their performance. The rise in frequency makes it possible to have short wavelengths so that it becomes possible to have a great integrationas as well as very fast bit rate. But, this induces a smaller range due to the propagation losses according to the model of Friis. In this article, a new patch antenna array for microwave frequency band in radio-frequency identification RFID applications will be presented. The antenna covers the band for the central frequency of 2.45 GHz with better loss characteristics. In addition, the antenna offers a high gain at this frequency. After the digital design of the antenna element, which was carried out using the commercial software CST MWS®, the antenna is printed on an FR4 substrate with a dielectric constant of 4.3 and a thickness of 1.6 mm. The comparison between the simulation results and the measurement results proves that the antenna achieves satisfactory impedance matching and radiation efficiency.